Queer studies: A lesbian, gay, bisexual & transgender anthology - Beemyn, Genny; Eliason, Michele J. (New York University Press, 1996)
This book is a wide-ranging anthology which discusses the nature and diversity of queer studies, its foundations, and some of the most pressing issues in the field.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identité sexuelle; identités; identités LGBTQIA2+; philosophie politique; postmodernisme; premier cycle; queer; sciences humaines; sex3383; sexualité; sociologie; thématiques

Queer theory: an introduction - Jagose, Annamarie (New York University Press, 1996)
The essential history of queer theory The reclamation of the term queer over the last several decades marked a shift in the study of sexuality from a focus on supposedly essential categories such as gay and lesbian, to more fluid notions of sexual identity. On the cutting-edge of this significant shift was Annamarie Jagose’s classic text Queer Theory: An Introduction. In this groundbreaking work, Jagose provides a clear and concise explanation of queer theory, tracing it as part of an intriguing history of same-sex love over the last century. Blending insights from prominent theorists such as Judith Butler and David Halperin, Jagose illustrates that queer theory's challenge is to create new ways of thinking, not only about fixed sexual identities such as straight and gay, but about other supposedly immovable notions such as sexuality and gender, and man and woman. First released almost 25 years ago, this groundbreaking work has provided a foundation for the continuing evolution of queer theory in the twenty-first century.
Keywords: approches et analyses; cours; discipline; histoire; premier cycle; queer; sciences humaines; soc2014; thématiques

Queer theory/sociology - Seidman, Steven (Twentieth-century social theory, 1996)
Bringing together some of the classic sociological statements and the new sociology of homosexual desire, this book points to new synthetic approaches to queer studies. It aims to productively engage the pioneering work of queer theorists.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; premier cycle; périodes historiques; queer; sciences humaines; soc2014; sociologie; sofia; thématiques